2018
DOI: 10.1161/circulationaha.117.030848
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Baseline Diastolic Blood Pressure on Effects of Intensive Compared With Standard Blood Pressure Control

Abstract: URL: https://www.clinicaltrials.gov. Unique identifier: NCT01206062.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
95
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 26 publications
13
95
1
Order By: Relevance
“…Our findings were similar to a recent study in which the authors analysed pooled data from ACCORD and SPRINT, and reported a J‐curve regarding the relationship between on‐treatment BP and cardiovascular outcomes. Whether or not the J‐curve phenomenon exists remains debatable . Recently, two large scale meta‐analyses which assessed the effects of BP lowering on cardiovascular outcomes reported the benefit of BP lowering even in patients with a baseline SBP <130 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were similar to a recent study in which the authors analysed pooled data from ACCORD and SPRINT, and reported a J‐curve regarding the relationship between on‐treatment BP and cardiovascular outcomes. Whether or not the J‐curve phenomenon exists remains debatable . Recently, two large scale meta‐analyses which assessed the effects of BP lowering on cardiovascular outcomes reported the benefit of BP lowering even in patients with a baseline SBP <130 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Heart Outcomes Prevention Evaluation (HOPE3) showed no benefit of BP lower less than 140/90 mmHg in patients with intermediate risk, which emphasizes the importance of addressing the CV risks when tailoring BP goals. One size may not fit all, the ESC/ESH guidelines goals may be more feasible in patients with poor vascular compliance, orthostatic hypotension, and high pulse pressures …”
Section: Current Evidence and Guidelinesmentioning
confidence: 99%
“…One size may not fit all, the ESC/ESH guidelines goals may be more feasible in patients with poor vascular compliance, orthostatic hypotension, and high pulse pressures. 33,43,65 The consensus documents looked at the same evidence and came up with different recommendations. When reviewing the data from the "minority view" paper in Annals there is a statistical type II misinterpretation of the data.…”
Section: Data From the Second National Health And Nutrition Examinationmentioning
confidence: 99%
“…A further analysis published in Circulation [22] in 2018 considered whether there was any effect of reducing diastolic pressure when targeting 120 mm Hg systolic. The results showed that when decreasing the baseline diastolic pressure a further reduction of blood pressure did cause an increase in mortality, but the mortality was still lower than with standard treatment.…”
Section: Hypertension: a J (Ton) Rabelink (The Netherlands)mentioning
confidence: 99%